Leader-Member Exchange across two hierarchical levels of leadership: concurrent influences on work characteristics and employee psychological health. - Karanika-Murray, Maria; Bartholomew, Kimberley J.; Williams, Glenn A.; Cox, Tom (Work & Stress)
Leader-Member Exchange (LMX) theory suggests that the quality of the leader–employee relationship is linked to employee psychological health. Leaders who reside at different hierarchical levels have unique roles and spheres of influence and potentially affect employees' work experiences in different ways. Nevertheless, research on the impact of leadership on employee psychological health has largely viewed leaders as a homogeneous group. Expanding on LMX theory, we argue that (1) LMX sourced at the levels of the line manager (LM) and senior management (SM) team will be differentially linked to employee psychological health (assessed as worn-out) and that (2) these relationships will be mediated by perceived work characteristics (reward and recognition, workload management, quality of relationships with colleagues and physical environment). Structural equation modelling on data from 337 manual workers partially supported the hypotheses. Perceptions of the physical environment mediated the relationship between LMX at the LM level and employee psychological health, whereas perceptions of workload management mediated the relationship between LMX at the SM level and psychological health. These findings corroborate arguments that leaders are not a uniform group and as such the effects of LMX on employees will depend on leadership hierarchy. Implications for expanding leadership theory are discussed.